2020
DOI: 10.1530/erc-19-0431
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase from myeloid cells promotes TSC2-null tumor growth

Abstract: Chronic inflammation promotes progression of many cancers, with circulating myeloid-derived suppressor cell (MDSC) levels correlating with poor prognosis. Here we examine effects of MDSCs on lymphangioleiomyomatosis (LAM), a rare disease occurring almost exclusively in women whereby estrogen-sensitive metastatic TSC2-null tumors grow throughout the lungs, markedly reducing pulmonary function. The LAM cell origin remains unknown; however, previous work demonstrated that Tsc2 inactivation in the mouse uterus ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
(72 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, further studies are still required to assess the exact role of ADAMs on tumor infiltrating neutrophils in the tumor microenvironment. CD8+T cell played a direct and clear role on tumor cell (Giese, Hind & Huttenlocher, 2019;Okada et al, 2020;Taya et al, 2020). Previous studies showed that CD8+T cell infiltration improved a survival benefit of the patient with advanced cancer (Vihervuori et al, 2019).…”
Section: Infiltration Levelmentioning
confidence: 96%
“…Therefore, further studies are still required to assess the exact role of ADAMs on tumor infiltrating neutrophils in the tumor microenvironment. CD8+T cell played a direct and clear role on tumor cell (Giese, Hind & Huttenlocher, 2019;Okada et al, 2020;Taya et al, 2020). Previous studies showed that CD8+T cell infiltration improved a survival benefit of the patient with advanced cancer (Vihervuori et al, 2019).…”
Section: Infiltration Levelmentioning
confidence: 96%
“…The exact contribution of neutrophils to tumorigenesis is not yet fully understood. Neutrophil-derived enzymes such as neutrophil elastase (NE) [ 17 , 18 ], the production of reactive oxygen species (ROS) [ 19 , 20 ] and reactive nitrogen species (RNS), as well as the immunosuppressive ability of a subset of neutrophils have all been reported to be implicated in tumor initiation. A tumor promoting role has also been attributed to neutrophils by in vivo studies.…”
Section: The Opposing Roles Of Neutrophils In Cancermentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ 7.37 (d, J = 8.6 Hz, 2H), 7.05 (d, J = 8.6 Hz, 2H), 5.10 (d, J = 9.0 Hz, 1H, NH), 4.88 (q, J = 6.4 Hz, 1H), 4.43 (dd, J = 9.2, 4.8 Hz, 1H), 2.31 (m, 1H), 1.46 (m, 12H), 1.07 (d, J = 6.8 Hz, 3H), 1.01 (d, J = 6.9 Hz, 3H). 13 4-(1-bromoethyl)phenyl (tert-butoxycarbonyl)valinate (10). To a stirred solution of 9 (2 g, 1 equiv, 5.96 mmol) in DCM at 0 °C were added CBr 4 (2.95 g, 1.5 equiv, 8.89 mmol) and triphenylphosphine (2.33 g, 1.5 equiv, 8.89 mmol).…”
Section: -( 1 -( ( D I -T E R T -B U T Y L a M I N O ) O X Y ) E T H ...mentioning
confidence: 99%